Paediatric Iliopsoas abscess: A case report. Issue 4 (November 2013) - Elliott, Carla
Abstract: Introduction : Iliopsoas abscess is an uncommon condition in the paediatric population. The clinical presentation is variable and may be confused with other conditions such as septic arthritis, osteomyelitis and appendicular abscess. A suspicion of iliopsoas abscess requires a prompt diagnosis so that rapid management and treatment can be undertaken. Discussion : This case describes the presence of an iliopsoas abscess in a paediatric patient presenting to the emergency department within a rural community. Due to the variability in clinical presentation imaging studies are necessary to distinguish an iliopsoas abscess from other inflammatory processes. Ultrasound is often the modality of choice. Imaging guided percutaneous drainage and/or aspiration and the administration of intravenous antibiotics are minimally invasive modern techniques providing a safe treatment options in the presence of an iliopsoas abscess. Conclusion : Iliopsoas abscess is an uncommon condition in the paediatric population. Due to the variability in clinical presentation, imaging, and in particular, ultrasound play a vital role in the diagnosis of cases with a high suspicion of abscess formation. Accurate diagnosis leads to a rapid treatment plan, avoiding further insult.